Schools and Language Barriers: Rural Schools Stories - Khairiah Syahabuddin (Bansigom Na Publisher, 2025)
This study explores the impact of language barriers on the educational experience of students in rural schools. In many rural areas, language differences between students and teachers can significantly affect learning outcomes, communication, and overall student performance. This research focuses on schools in rural regions where minority languages or dialects are spoken, and the medium of instruction is often a different language. Through interviews with teachers, students, and community members, this study aims to understand the challenges posed by language barriers, the coping strategies employed by teachers, and the support systems available to students. The findings suggest that language barriers contribute to academic difficulties, social isolation, and low self-esteem among students, but various interventions, such as bilingual education, community involvement, and teacher training, can help mitigate these challenges. This study highlights the need for tailored educational strategies and policy interventions to address language barriers in rural schools, ensuring more equitable access to quality education for all students.